Pendampingan Permainan Congklak terhadap Pemahaman Penjumlahan Anak Sekolah Dasar Kelas 2 dan 3 Di Desa Gombong - Nawa Fazliani; Ajeng Muliasari; Mia Minhatul Ma’arif; Linda; Asep Saefullah Kamali; Ismi Widyaningrum (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
Mathematics in elementary schools studies basic arithmetical sciences as a provision for students to understand education at a further level. For this reason, teachers are expected to be able to create an interesting and fun learning atmosphere. One of them is through innovation in learning media. Learning media is one of the determinants of the success of the learning process. Learning media is one of the determinants of the success of the learning process (Agusti, Afirah, Anwar, & Syafril, 2018). The community service method is in the form of assistance in traditional game-based mathematics learning, namely participatory action research (PAR). PAR is a service method for finding solutions to societal problems, which are trying to be solved jointly by the service team and interested parties. This service was once carried out at the KKN-T post in Gombong village for students in grades 2 and 3. Students in grades 2 and 3 were enthusiastic the first time they took math lessons. This assistance provided a platform for children in the Gombong village to learn mathematics through cultural games that have started to be eliminated with IT-based games. In addition, the suggestion is that teachers can take advantage of culture in facilitating mathematics learning in schools so that children can not only understand learning material but also cultivate a way of loving traditional culture.